2013
DOI: 10.1021/cm402179h
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down versus Bottom-Up Fabrication of Graphene-Based Electronics

Abstract: Graphene electronic devices can be made by top-down (TD) or bottom-up (BU) approaches. This Perspective defines and explains those two approaches and discusses the advantages and limitations of each, particularly in the context of graphene fabrication. It is further exemplified using graphene nanoribbons as the prototypical graphene structure that can be prepared using either a TD or BU approach. The TD approach is well-suited for placement of large arrays of devices on a chip using standard patterning tools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
141
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(144 citation statements)
references
References 52 publications
(93 reference statements)
0
141
1
2
Order By: Relevance
“…However, although the current CNT oscillator in GNR trench is difficult to implement by simple processes, we should note that such a structure can be achieved by the nanotube-graphene hybrid nanofabrication processes, as discussed in the Introduction [40][41][42][43][44][45][46][47][48].…”
Section: Oscillatory Behaviors Of Cnt-oscillatormentioning
confidence: 99%
See 1 more Smart Citation
“…However, although the current CNT oscillator in GNR trench is difficult to implement by simple processes, we should note that such a structure can be achieved by the nanotube-graphene hybrid nanofabrication processes, as discussed in the Introduction [40][41][42][43][44][45][46][47][48].…”
Section: Oscillatory Behaviors Of Cnt-oscillatormentioning
confidence: 99%
“…Quite recently, fullerene-graphene hybrids have been experimentally produced and theoretically investigated [34][35][36][37][38][39]. In particular, nanotube-graphene hybrid also has great potential application [40][41][42][43][44][45][46][47][48]. Theoretical work suggested that a covalently bonded graphene-nanotube hybrid material would extend those properties to three dimensions, and be useful in energy storage and nanoelectronic technologies [40].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these include the need to create a band gap (as discussed earlier), which limits its applications in high-performance integrated logic circuits and the contact resistance between graphene and other electrode materials. For these reasons, it has been suggested that the controlled integration of graphene layers into circuits using a top-down, bottom-up, or hybrid approach [115] is likely to appear after 2020 [95].…”
Section: Graphene In Molecular Electronicsmentioning
confidence: 99%
“…Likewise, graphene sheets (GSs) had received various attentions in efforts to develop high-performance functional materials [3], mainly including transistors, photovoltaic electrodes, resonators, and ultracapacitors [4][5][6]. There were two typical approaches that had been employed to synthesize GS materials [7]. The ''bottom-up'' approach allowed tuning of the fine structure of GSs, such as shape, size, and location of defects [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There were two typical approaches that had been employed to synthesize GS materials [7]. The ''bottom-up'' approach allowed tuning of the fine structure of GSs, such as shape, size, and location of defects [7,8]. This approach had established a basis for bandgap control, supramolecular assembly, and device applications of GSs.…”
Section: Introductionmentioning
confidence: 99%